Prototipe Sistem Keamanan Ganda Pada Kendaraan Roda Dua Berbasis Android dan WhatsApp Messenger - Fatimah Fahurian; Hilda Dwi Yunita; Khozainuz Zuhri; Yodhi Yuniarthe (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2021)
Entering 2020, the corona virus outbreak is spreading very quickly throughout the world, including Indonesia. This encourages the Indonesian government to make efforts and take handling policies to suppress the global spread of the corona virus or Covid-19. These policies did reduce the number of spreads but created new problems, such as increasing criminal acts and coupled with assimilation rights policies (freeing prisoners) during the Covid-19 pandemic which also resulted in an increase in crime rates, such as theft with weighting, motor vehicle theft, theft accompanied by violence, mugging, to beheading. One of the reasons for the increase in theft cases is the use of the situation when everyone is focused on handling Covid-19 and also the existence of security gaps. The security gap can be minimized, one of which is by developing technological innovation, therefore the author proposes a prototype for the development of a dual security system on two-wheeled vehicles with the latest technology. The results of the study, the system can provide notification information through the WhatsApp Messenger application in real time, as well as vehicle owners can control the vehicle remotely using the android application.